Peran Kepemimpinan Kepala Sekolah Di Era 5.0 - Mardiyyah, Nadwah Hidayatul; Ijudin, Ijudin (Universitas Garut, 2023)
In this study, it discusses the Leadership Role of the Principal in the 5.0 Era. This study uses a qualitative research method which is an emphasis in the analysis on descriptive data in the form of words which are of course observed. researchers use formal research objects and materials. The formal object in this study is in the form of a data, while in the material object, it is in the form of a source in a data. According to these results, it can be concluded that a leader in an educational institution must be able to follow all aspects of digital development, so that there are no stages left behind in any aspect. A leader in an educational institution is a factor in the success or failure of an educational institution. So that this can be used as a means to increase progress by using increasingly rapid technology.